2022
DOI: 10.1021/acsami.2c08418
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Oxygen Species in Low-Temperature Catalytic o-Xylene Oxidation on MOF-Derived Bouquetlike CeO2

Abstract: To realize efficient low-temperature catalytic o-xylene oxidation, MOF-derived CeO2-X catalysts were prepared via the pyrolysis of MOF precursors with different ratios of cerium nitrate to trimesic acid. Among the synthesized catalysts, the bouquet like CeO2-1 exhibited the best activity with T 50 and T 90 of 156 and 198 °C and the lowest activation energy of 60.67 kJ·mol–1 (WHSV= 48 000 mL·g–1·h–1, o-xylene concentration = 500 ppm). o-Xylene was completely mineralized, and no change in conversion efficiency o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 61 publications
(109 reference statements)
1
11
0
Order By: Relevance
“…Notably, the H 2 O, ν(t-OH) or Ce 3+ band area which highlights surface cerium reduction under H 2 , showed that the reaction had already begun at RT. This is in line with cerium’s higher reducibility in the case of MOF-derived CeO 2 samples [ 26 , 27 , 28 , 29 ].…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…Notably, the H 2 O, ν(t-OH) or Ce 3+ band area which highlights surface cerium reduction under H 2 , showed that the reaction had already begun at RT. This is in line with cerium’s higher reducibility in the case of MOF-derived CeO 2 samples [ 26 , 27 , 28 , 29 ].…”
Section: Resultssupporting
confidence: 71%
“…The increase in the onset temperature with the Zr content was related to the known higher stability of pure Zr-UiO-66 [ 58 ]. MOF calcination was then conducted at 450 °C to eliminate the organic components, in line with the temperatures range reported in the literature [ 26 , 27 , 28 , 29 ]. C100-UiO-66 calcination could have been conducted at lower temperature (≈350 °C); however, this would have induced an inhomogeneity in the samples’ thermal treatments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, biological treatment is regarded as an emerging technology for VOSCs degradation as it has been proven to be adaptable to VOSCs waste gas conditions, including low concentration, large flow rate, high moisture, and the required degradation rate of PT. Unfortunately, the biological control of VOSCs still meets the low removal load bottleneck, which results from their low solubility and biotoxicity . In other words, both the mass transfer and reaction steps involved in the biological treatment of VOSCs waste gas are still hindered.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the mixed Cu–Mn oxide obtained by direct calcination of metal salt in open space, the ordered Cu–Mn oxide prepared by the hard template route showed a high surface area and a rich porous structure, further leading to much better activity in the catalytic removal of carcinogenic benzene. Besides, some new precursors like metal–organic frameworks (MOFs) have been applied as a self-sacrificing template for synthesizing porous nanostructures via pyrolysis of organic components, where the obtained nanostructure with a high surface area and rich active species displayed much better low-temperature activity. However, it is still a great challenge to get the porous oxides on a large scale due to the complicated procedure of the templating approach and costly precursors like MOF components.…”
Section: Introductionmentioning
confidence: 99%